Impacts of Climate Change on Agriculture for Local Paddy Water Requirement Irrigation Barito Kuala, South Kalimantan, Indonesia - Maya Amalia Achyadi; Koichiro Ohgushi; Toshihiro Morita (Center for Journal Management and Publication, 2019)
Increasing rice consumption demand in Indonesia has provided serious problems such as food insecurity. Being the major staple food, rice production is the main priority of medium and long term development planning in Indonesia. Local rice production is strongly affected by climate conditions, especially in South Kalimantan. Nowadays, the world must adjust to climate change. One of significant effects of changing climate on agriculture is related to productivity. Evapotranspiration is the major cause of loss of water needed, for agricultural requirements. The crop requires effective irrigation system with adequate water amount. The main objective of this research is to analyze the water requirements for the irrigation units in Barito Kuala, South Kalimantan concerning local rice cultivation under the climate change scenarios. Supposed rainfall during the 2050s and 2090s are obtained from four downscaled circulated models and one model for projected temperature under CMIP5 with RCPs 8.5 scenario. Penman-Monteith method was usedÂ to calculate the evapotranspiration value. Based on future effective rainfall water requirement is estimated.Â The result shows the impact of climate change on the water irrigation requirement of local paddy cultivation are 56% and 25 % higher than current condition in July and September October respectively.